Ethene adsorption and dehydrogenation on clean and oxygen precovered Ni(111) studied by high resolution x-ray photoelectron spectroscopy - Lorenz, Michael Peter Andreas; Fuhrmann, Thomas; Streber, R.; Bayer, Andreas; Bebensee, Fabian; Gotterbarm, Karin; Kinne, Martin; Tränkenschuh, Barbara; Zhu, J. F.; Papp, Christian; Denecke, R.; Steinrück, Hans-Peter (Journal of Chemical Physics, 2010)
The adsorption and thermal evolution of ethene (ethylene) on clean and oxygen precovered Ni(111) was investigated with high resolution x-ray photoelectron spectroscopy using synchrotron radiation at BESSY II. The high resolution spectra allow to unequivocally identify the local environment of individual carbon atoms. Upon adsorption at 110 K, ethene adsorbs in a geometry, where the two carbon atoms within the intact ethene molecule occupy nonequivalent sites, most likely hollow and on top; this new result unambiguously solves an old puzzle concerning the adsorption geometry of ethene on Ni(111). On the oxygen precovered surface a different adsorption geometry is found with both carbon atoms occupying equivalent hollow sites. Upon heating ethene on the clean surface, we can confirm the dehydrogenation to ethine (acetylene), which adsorbs in a geometry, where both carbon atoms occupy equivalent sites. On the oxygen precovered surface dehydrogenation of ethene is completely suppressed. For the identification of the adsorbed species and the quantitative analysis the vibrational fine structure of the x-ray photoelectron spectra was analyzed in detail. © 2010 American Institute of Physic